Analisis Bentuk dan Makna Ungkapan Sindiran Guru Bahasa Indonesia Terhadap Siswa Kelas X, XI dan XII di SMA Negeri 2 Kupang - Wake, Sajer Karun Tu Love; Djuli, Labu; Makan Malay, Narantoputrayadi (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This research focuses on the forms and meanings of the Indonesian language teacher’s ironical expressions toward students of grades X, XI, and XII at SMA Negeri 2 Kupang. The aim of this study is to identify and describe the forms of ironical expressions used by the Indonesian language teacher toward the students. The data analyzed consists of utterances or communicative interactions made by the Indonesian language teacher at SMA Negeri 2 Kupang during the learning process. The research employs a descriptive qualitative method, with data analysis presented descriptively. This study is based on the stylistics theory of Gorys Keraf as the foundation for analysis. The research findings reveal four forms of ironical expressions, including irony, sarcasm, cynicism, and antiphrasis. The meanings of these expressions generally include both denotative and connotative meanings, containing criticism, warnings, and reprimands.